A tiny lesion arising within Barrett’s esophagus - Pugliese, Francesco; Bonato, Giulia; Dioscoridi, Lorenzo; Cintolo, Marcello; Aquilano, Maria Costanza; Forti, Edoardo; Giannetti, Aurora; Italia, Angelo; Mutignani, Massimiliano (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Pugliese F, Bonato G, Dioscoridi L, et al. A tiny lesion arising within Barrett’s esophagus. Turk J Gastroenterol 2020; 5: 410-2.